THE PECULIARITY OF INVESTMENT COOPERATION OF THE REPUBLIC OF KAZAKHSTAN WITH PEOPLE’S REPUBLIC OF CHINA (International Journal of Innovative Technologies in Economy, 2019)
Investment cooperation between Republic of Kazakhstan and People’s Republic of China is, first of all, that, being mutually beneficial, it provides for different in nature economic results for the interacting parties. China, as a result of this cooperation, is pursuing a solution to the problem of maintaining sustainable economic development. For Republic of Kazakhstan, investment cooperation with People’s Republic of China should contribute to further maintaining sustainable economic growth and modernizing the national economy in order to effectively participate in the system of world economic relations.Since 2015, investment flows from China to Kazakhstan have shown positive dynamics, their average annual growth is 22%. At the same time, the largest volume of FDI falls on 2018: $ 1.5 billion - 37.6% more than in 2017, and 78.6% more than in 2015. For the first half of 2019, the gross inflow of investments from China amounted to 362 million US dollars.In the Republic of Kazakhstan from 2015 to 2019, Kazakh-Chinese projects are implemented for a total amount of $ 35 billion. During this period, 10 enterprises were launched.